A rural emergency medical retrieval service: the first year. Issue 9 (18th August 2006) - Corfield, A R; Thomas, L; Inglis, A; Hearns, S
Abstract : Introduction: We describe the first year of operation of a rural emergency medical retrieval service (EMRS), staffed by emergency medicine and anaesthetic consultants and providing air based retrieval of critically ill and injured patients from general practitioner led community hospitals in rural west Scotland. Methods: Data were collected on all patients referred to the service, both those subsequently transported and those where transport by the service was not indicated, for a period of 1 year from 1 October 2004 to 30 September 2005. Data collected included information on demographics, physiology, and medical interventions. Detailed data were collected regarding advanced airway care and any complications relating to transfer. Results: Forty patients were attended and advice was given on a further 21 patients. Twenty one of the 40 patients (53%) required rapid sequence intubation prior to transfer. The median Injury Severity Score (ISS) for trauma patients was 26 (range 2–59). The median Acute Physiology and Chronic Health Evaluation (APACHE) II score for all patients was 11 (range 2–37). Conclusion: Our data show a high level of acuity among this patient group and a need for advanced medical intervention to ensure safe transfer.